Sustainable hydrate production using intermittent depressurization in hydrate-bearing reservoirs connected with water layers - He, Juan; Li, Xiaosen; Chen, Zhaoyang; You, Changyu; Peng, Hao; Zhang, Zhiwen (Energy, 2022)
The intermittent depressurization may sustain hydrate production. But its production features and influencing factors in the real setting have not been clear. Thus, the intermittent depressurization with the participation of the water layers was performed in the laboratory samples. The hydrate production features were studied from pressure changes, temperature changes, gas and water production, multiphase flow, and residual hydrates. On the other hand, the influencing factors were analyzed from the back pressure, the recovered pressure, and the retarded temperature recovery. The results showed that gas and water production was increased by 44.05 % and 97.14 %, respectively. The abnormal depressurization, the fresh hydrate formation, and the retarded temperature recovery were observed. Moreover, hydrate dissociation and gas flow were weakened by the thickened water films around hydrate grains and the quick depressurization along with the preferential flow channels. Hence, residual hydrates accounting for 49.15 % were still found after the intermittent depressurization. Besides, the back pressure of 2.6 MPa increased gas production by 22.915 L; the recovered pressure of 3.92 MPa reduced water production by 47.85 %; the wait for temperature recovery increased hydrate dissociation rate of 15.29 %. This work may benefit the achievement of the sustainable hydrate production in actual hydrate reservoirs. (c) 2021 Elsevier Ltd. All rights reserved.